Male basketball players who report hip and groin pain perceive its negative impact both on- and off-court: A cross-sectional study. Issue 7 (July 2021) - Dooley, Katherine; Drew, Michael K.; Snodgrass, Suzanne J.; Schultz, Adrian; McGann, Tye; Blyton, Sarah; Pizzari, Tania; Rio, Ebonie; Donnan, Luke; Edwards, Suzi
Abstract: Objectives: To identify if basketball players aged <20 years (U20) self-report hip and/or groin pain and if they perceive this as a problem. To determine potential differences in self-reported playing (training and match play) loads and Copenhagen Hip and Groin Outcome Score (HAGOS) between those with and without hip/groin pain. Design: Cross-sectional. Methods: Fifty-one pre-elite (state/national representative level) male U20 basketball players (Australian n = 38; Italian n = 13) self-reported current/historical hip/groin 'discomfort/pain' and 'problems', and playing loads. A two-factor regression model was fitted including main effects for hip/groin pain and Cohort and their interaction, with outcome variables playing loads and HAGOS subscale scores and dependent variable hip/groin pain. Results: Twenty-one players (41%) self-reported hip/groin 'discomfort/pain', of which nine perceived no 'problems'. Two of these nine players reported training/playing time loss due to pain. Those self-reporting hip/groin discomfort/pain scored lower than those without in HAGOS subscales Symptoms (mean difference in score 8.94; 95%CI −25.24, −5.97), Pain (5.00; −16.42, −2.81), Function in daily living (0.00; −26.72 to −5.59), Function in sport and recreation (6.25; −21.24, −5.33), and hip and/or groin Quality of Life (5.00; −28.63, −8.10), indicating worse hip/groin problems. Participation subscale scores were different only for Italian players (36.25; −51.25, −20.00), with players self-reporting hip/groin discomfort/pain scoring lower. Conclusion: Most players who perceive both hip/groin 'discomfort/pain' and 'problems' also report training/playing time loss, suggesting players' perceptions of problematic symptoms and time-loss are associated. Adolescent basketball players perceive hip/groin pain to negatively impact their daily lives and sporting function.